Sustainability Indices and the Calendar Effect - K. Kalimuthu; S. Shaik (Финансы: теория и практика)
The investing landscape has undergone a significant shift. Investors are interested in stocks that not only increase shareholder  wealth  but  also  give  high  priority to  environmental, social, and  governance  issues. The  purpose  of the study is to examine the  presence  of  a  calendar  effect  on  the  BSE  sustainability  indices. The  daily  closing prices  of  the  BSE  CARBONEX, BSE  GREENEX, BSE 100, BSE  Sensex, and  Nifty have  been  collected. The  study is using various methods like descriptive statistics, the unit root test, the day of the week return, the ordinary least squares method (OLS), and the GARCH (1, 1) model. It  is  clear  from  the  study results  that  sustainability index returns follow the pattern of the BSE 100 and Sensex. There is a high positive and statistically significant Tuesday effect during the full sample period and period II. The GARCH (1, 1) model indicates there is a significant Monday effect on all indices. The result obtained in this paper is useful to investors to frame their investment strategy, for academicians to study the performance of the indices for different periods, and for business people to know the trend and tendencies.